Analisis Cover Album “Savage” Dari Girl Group Aespa - Salsabila Hamza; Jupriani Jupriani (Jurnal Kajian dan Penelitian Umum, 2023)
The research aims to understand the visual form and meaning of the album "Savage" by girl group Aespa. It is hoped that this study can be useful as a new knowledge base and can be used as a future research reference. To achieve these goals and benefits, the author uses a descriptive qualitative approach. An analysis of this study was conducted with the semiotics theory of Charles Sanders Pierce. The resources obtained are primary data obtained directly from SYNK DIVE's physical album "Savage" and interview process, while secondary data are from various literature sources. The results that the authors obtained after conducting this study were the album's cover design to visualize the contents of the songs and concepts on the album. The album's cover was designed using a flow of futurism that describes the speed of a movement.